Non-targeted metabolomics characterization of Annona muricata leaf extracts with anti-angiogenic activity - Cárdenas García, Casimiro; Torres-Vargas, José Antonio; Cárdenas Valdivia, Abel; Jurado, Nuria; Rodríguez-Quesada, Ana María; García-Caballero, Melissa; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel (Elsevier, 2021)
The tropical plant Annona muricata has been widely used for traditional ethnobotanic and pharmacologic applications. Extracts from different parts of this plant have been shown to have a wide range of biological activities. In the present study, we carry out a metabolomic study of both aqueous and DMSO extracts from Annona muricata leaves that has allowed us to identify 33 bioactive compounds. Furthermore, we have shown that aqueous extracts are able to inhibit endothelial cell migration and both aqueous and DMSO extracts inhibit the formation of tubule-like structures by endothelial cells cultured on Matrigel. We conclude that extracts of Annona muricata leaves have great potential as anti-angiogenic natural combinations of bioactive compounds.
Keywords: Neovascularización; Ultra-high-performance liquid chromatography-high-resolution mass spectrometry (UHPLC–HRMS); Annona muricata; Graviola; Soursop; Angiogenesis